A tree frog (Boana pugnax) dataset of skin transcriptome for the identification of biomolecules with potential antimicrobial activities - Yamil Liscano Martinez; Claudia Marcela Arenas Gómez; Jeramiah Smith; Jean Paul Delgado (Data in Brief, 2020)
Increases in the prevalence of multiply resistant microbes have necessitated the search for new molecules with antimicrobial properties. One noteworthy avenue in this search is inspired by the presence of native antimicrobial peptides in the skin of amphibians. Having the second highest diversity of frogs worldwide, Colombian anurans represent an extensive natural reservoir that could be tapped in this search. Among this diversity, species such as Boana pugnax (the Chirique-Flusse Treefrog) are particularly notable, in that they thrive in a diversity of marginal habitats, utilize both aquatic and arboreal habitats, and are members of one of few genera that are known to mount a robust immunological response against the fungus Batrachochytrium dendrobatidis, which has decimated the population of frogs worldwide. To search for molecules with potential antimicrobial activity, we have assembled and annotated a reference transcriptome from the skin of four wild captured B. pugnax from Antioquia, Colombia. Analysis of potential antimicrobial and immunological components was performed using ontology analyses, we identified several antimicrobial chemokines with particularly strong potential for exhibiting broadscale antimicrobial activities, as well as several genes related to rapid alteration of transcriptional (KRAB zinc finger protein) and phosphorylation (MAPK) responses to exogenous stressors. We also found eight families of transmembrane transport proteins, including sodium, potassium and voltage-dependent calcium channels, which will be invaluable in future studies aimed at more precisely defining the diversity and function of cationic antimicrobial peptides with alpha-helical structures. These data highlight the utility of frogs such as Boana pugnax in the search of new antimicrobial molecules. Moreover, the molecular datasets presented here allow us to expand our knowledge of this species and illustrate the importance of preserving the vast potential of Colombian biodiversity for the identification of useful biomolecules.